The role of merger in creating differences in the profitability of companies Analytical research between a sample of subsidiaries to the Iraqi Ministry of Industry and Minerals - سعيد عبد السلام لفته; خلف امين زيدان (Journal of Economics and Administrative Sciences, 2020)
The research aims to identify the impact of the merger of the companies affiliated to the Ministry of Industry and Minerals on their financial profitability since the companies before the merger suffered a rise in losses and the deficit reached very high levels that affected its overall performance and even on the morale of workers as losses are increasing and solutions Efficiency is absent. The problem stems from knowing the impact of the merger on the profitability ratios of the companies. The research field was represented by the companies affiliated to the Ministry of Industry and Minerals (21) companies, while the research sample reached (6) companies after the merger (14) companies before the merger, was based on data The financial period from (2011 to 2015) before the merger and (2016 and 2017) after the merger, in addition to the method of personal observation and interview, the researcher relied on the analytical method and based on some statistical tools such as the Wilcoxon test of significance (0.05) as well as the arithmetic averages. The presence of significant differences in the rate of return on a Assets of companies (General Company for Electronic Systems, General Company for Design and Execution of Projects, General Company for Steel Industries and General Company for Electrical and Electronic Industries), which are symbolized (G1, G3, G4, G5) respectively, excluding the two companies (General Company for Food Industries and General Company for Mining Industries) which (G2, G6) respectively there were significant differences due to the improvement in net sales of companies after the merger and the good utilization of the assets. The absence of significant differences in the rate of return on the right of ownership of all companies sample research except the General Company for Food Industries G6 It was found that the merger has a positive impact on its financial performance, especially through improvement in net sales than it is before the merger, and therefore the researcher recommends the need to search for ways that lead To increase the net profit and reduce operating expenses and good utilization of assets of the company with the need to balance between liquidity and profitability. As well as working to find ways to increase the market share, as well as the competent authorities to adjust the capital of companies to be to the extent commensurate with the moral value of these companies